Predicting IVIG resistance in UK Kawasaki disease. Issue 4 (10th February 2015) - Davies, Sarah; Sutton, Natalina; Blackstock, Sarah; Gormley, Stuart; Hoggart, Clive J; Levin, Michael; Herberg, Jethro A
Abstract : The Kobayashi score (KS) predicts intravenous immunoglobulin (IVIG) resistance in Japanese children with Kawasaki disease (KD) and has been used to select patients for early corticosteroid treatment. We tested the ability of the KS to predict IVIG resistance and coronary artery abnormalities (CAA) in 78 children treated for KD in our UK centre. 19/59 children were IVIG non-responsive. This was not predicted by a high KS (11/19 IVIG non-responders, compared with 26/40 responders, had a score ≥4; p=0.77). CAA were not predicted by KS (12/20 children with CAA vs 25/39 with normal echo had a score ≥4; p=0.78). Low albumin and haemoglobin, and high C-reactive protein were significantly associated with CAA. The KS does not predict IVIG resistance or CAA in our population. This highlights the need for biomarkers to identify children at increased risk of CAA, and to select patients for anti-inflammatory treatment in addition to IVIG.